PERBANDINGAN DATA PENJULAN MULTIVITAMIN DI APOTEK “X” KECAMATAN TARIK KABUPATEN SIDOARJO SEBELUM PANDEMI (PERIODE JANUARI 2020) DAN DISAAT PANDEMI (PERIODE JANUARI 2021) - Ainun Mardiah; M. Rizky Arif (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
At the end of 2019 the world was shocked by a new virus variant, namely SARS COV2 or Covid-19, which started as an epidemic in Wuhan, China. With more and more people infected with this virus and it has spread to other countries, in 2020 WHO declared the status of the Corona Virus outbreak to be a pandemic, WHO hopes that countries in the world can take extra handling of this outbreak. Management of drug management and sales as a form of preventing the spread of the Covid-19 virus in health services as an effort to protect themselves from the transmission of the Covid-19 virus, thus making the current conditions require personal treatment through pharmacies against the Covid-19 pandemic that hit. Moreover, multivitamin drugs are needed for endurance during the pandemic. The role of pharmacies is very important in providing a very increasing drug availability. Methods: This study uses observation and in-depth interviews. In determining the number of samples using the total sampling technique. The instrument used was a data collection sheet (Observation) and interviews with pharmacist X pharmacy, Tarik sub-district. Results: the results of research on the comparison of multivitamin sales data at the